Exploring attitudes to decolonising the science curriculum-A UK Higher Education case study. - Lena Grinsted; Catherine Murgatroyd; Jodi Burkett (PLoS ONE)
Scientific advances are historically linked to colonial actions of past empires resulting in knowledge production biased towards the West with minimal representation of scholars of other ethnicities than White in science curricula in Higher Education (HE). Calls to decolonise science curricula seek to diversify content by acknowledging the role of racism and privilege in the history of science, aiming at creating a HE that is less isolating for minoritised ethnicities and feels welcoming to students of all identities. This case study explored science teaching staff's familiarity with and misconceptions of decolonisation at a UK HE institution using an online questionnaire. We further assessed participants' perceptions of barriers, benefits and risks, training needs, and preparedness to take actions in their teaching. We found that a majority of participants had a positive disposition towards decolonising their teaching, but that critical misconceptions, e.g. linking decolonisation to 'cancel culture' and 'colour-blind' behaviour were common, while important barriers, e.g. a lack of training and constraints on time, halt progress. We provide specific recommendations for staff training and a brief historical background relevant to life sciences. By supporting teachers, that train future generations of scientists, to decolonise the curriculum we can improve equity in HE, academia, and society.